Educational Aspiration, Dropout and TEVT - Acharya, Laxman (Journal of Training and Development, 2016)
This paper explores and discusses the root causes of dropout in an ethnic community in Nepal and then suggests of mandating technical and vocational education in secondary level education as one of the solutions that increases both efficiency and output of education system. In doing so, I carried out an ethnographic research as the part of my Ph.D, in ethnic community of Tamang people in one rural areas of Kathmandu district. I applied prolong field observation and in depth interview to explore their perception regarding school education. I came with the understanding that people had very low level of aspiration from existing school education. People were experienced only two roles of education in their life. First, many community people perceived role of education for them was nothing more than getting literacy skills: read and calculate. Second, some other people thought that school education was useful to increase the little hope of getting the low level of job. However having simply the school level certificate had no guarantee of getting a job. It needed to have a good network or to bribe the people who were in power. In order to materialize these two aspirations, grade 8 was enough so they were not bothered for completing school level education. However a very few community people considered school education as a foundation for higher education to lead to gain power, prestige and property. In this regard, I argue that mandating technical and vocational education in secondary level education that helps not only to fulfill the basic aim of education of developing employability among school graduates but also enhance the efficiency and outcome of school education system.